Imigração brasileira na Austrália: tensões e contradições nos processos de construção identitária e no ensino de português como língua de herança - O'Keeffe, Sandra Regina de Oliveira [UNIFESP] (2024)
Migrations and population movements, presents in the human history since its origins, have become increasingly frequent in recent years due to technological advances and the constant changes that the influence of globalization has been promoting on the world stage. New multiethnic landscapes and new configurations of multilingual and transcultural practices then emerge, considering that migrants take with them components of their identity such as their language and culture, which in a translocal situation are both in conflict between fragmentation and reaffirmation. Because of that it becomes necessary to understand how these people are dealing with the complexity of these changes and what meaning they are seeking to give to their new identities and subjectivities, now uncharacterized. Considering the growing diaspora of Brazilians heading to Australia, this work seeks to understand how the linguistic aspect has been shaped in this process, evaluating the specificities of the Australian context and the profil